Operators of the α-Bloch space on the open unit ball of a JB*-triple - HONDA, Tatsuhiro (Studia Universitatis Babeș-Bolyai Mathematica, 2022)
Mathematics Subject Classification (2010): 32A18, 32M15.Received 18 December 2021; Accepted 20 December 2021.